Investigation of ball burnishing processing on mechanical characteristics of wooden elements. (January 2017) - Babic, M; Kocovic, V; Vukelic, D; Mihajlovic, G; Eric, M; Tadic, B
Numerous research results indicate that the finishing processing of metal materials using ball burnishing has positive effects from the aspect of surface roughness decrease to the hardness increase in the surface layers of the processed materials. Little research has been devoted to this type of processing for nonmetal materials. This paper presents research results related to the influence of ball burnishing processing on the hardness increase of a wooden element. It was determined that the hardness can be increased up to three times for processing of wood using this technology, which is not the case for processing of metal materials.